2020
DOI: 10.3390/agronomy10050702
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Root Temperature on the Plant Growth and Food Quality of Chinese Broccoli (Brassica oleracea var. alboglabra Bailey)

Abstract: Root temperature has long been considered an essential environmental factor influencing the plant’s physiology. However, little is known about the effect of root temperature on the quality of the food produced by the plant, especially that of horticultural crops. To fill this gap, two independent root cooling experiments (15 °C vs. 20 °C and 10 °C vs. 20 °C) were conducted in autumn 2017 and spring 2018 in hydroponics with Chinese broccoli (Brassica oleracea var. alboglabra Bailey) under greenhouse conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 69 publications
(96 reference statements)
2
16
1
Order By: Relevance
“…Similarly, several previous studies suggested that, under drought stress, the reduction in plant growth attributes is accompanied with a reduction in plants turgor pressure, cell division, cell wall biosynthesis, and cell expansion (B. Li, Feng, et al, 2020; Pakdel et al, 2020; Zaid et al, 2020). A wealth of literature provided ample evidence that drought stress adversely affected plant biomass (shoot and root fresh and dry biomass) in addition to water content in Brassicaceae species (Bhuiyan et al, 2019), B. napus (Dai et al, 2020), B. carinata (Samanta et al, 2020), and B. oleracea (He et al, 2020). The loss of chlorophyll and photosynthesis can also cause a decrease in plant fresh and dry biomass under drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several previous studies suggested that, under drought stress, the reduction in plant growth attributes is accompanied with a reduction in plants turgor pressure, cell division, cell wall biosynthesis, and cell expansion (B. Li, Feng, et al, 2020; Pakdel et al, 2020; Zaid et al, 2020). A wealth of literature provided ample evidence that drought stress adversely affected plant biomass (shoot and root fresh and dry biomass) in addition to water content in Brassicaceae species (Bhuiyan et al, 2019), B. napus (Dai et al, 2020), B. carinata (Samanta et al, 2020), and B. oleracea (He et al, 2020). The loss of chlorophyll and photosynthesis can also cause a decrease in plant fresh and dry biomass under drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…In hydroponically grown carrots, a 14-day treatment with an elevated nutrient solution temperature increased the total phenolic compounds and soluble solid content [10]. Similarly, our previous studies of the effects of root temperature on food quality of Chinese broccoli [14] and cocktail tomato [15] have shown that long-term root cooling can be used as a strategy to accumulate high levels of phytochemicals such as sugar, chlorophyll, lycopene and glucosinolates with potential practical applications.…”
Section: Introductionmentioning
confidence: 62%
“…Intact individual glucosinolates were determined as described by He et al [14]. Briefly, approximately 60 mg of homogenized frozen leaf and stem samples of Exp-1 and Exp-2 were used for the extractions.…”
Section: Glucosinolates Analysismentioning
confidence: 99%
See 2 more Smart Citations